Islamic Scientific Critical Consciousness as a theoretical framework for Muslim science educators (UCL Press, 2024)
The suppression of Indigenous knowledge systems that accompanied the colonisation of Muslim lands from North Africa to the Asia-Pacific dismantled the Islamic science tradition, replacing it with a Western oppressive monoculture of secularised 'modern' science. Within this context, this article presents a theoretical framework for Muslim science educators, called Islamic Scientific Critical Consciousness. This framework aims to nurture Muslim students to develop the capacity to reinvigorate the Islamic science tradition by taking the positive elements of both the tradition and those of modern science. This entails the need for Muslim students to develop the critical consciousness to recognise colonial ideology being taught as 'objective' knowledge and the confidence and ethical orientation to pursue scientific research in harmony with an all-encompassing Islamic world view. This framework builds on Maldonado-Torres's framework of decoloniality by adapting it to consider the sources of oppressive ideologies from an Islamic perspective in the monocultural school science classroom. The learning outcomes for this Islamic decolonial approach are then developed by integrating Paolo Freire's idea of critical consciousness with Muhammad Iqbal's idea of Khudi (selfhood). After building the theoretical framework, suggestions are made on how modern science education can be rethought in both multifaith and Islamic faith-based school settings.